Federated Digital Twin Implementation Methodology to Build a Large-Scale Digital Twin System - Baek, Myung-Sun; Jung, Euisuk; Park, Young Soo; Lee, Yong-Tae (IEEE International Symposium on Broadband Multimedia Systems and Broadcasting, 2024)
This paper considers an implementation methodology for large-scale digital twin system. In our research, federated digital twin implementation methodology is proposed to build the large-scale digital twin system. In the proposed methodology, multiple single digital twin system can be connected and the output data of the multiple digital twin systems is federated. Typically, a single digital twin system is developed to digitally mimic a single physical object, system, or single process. Therefore, in the proposed methodology, the large-scale digital twin can be implemented based on federation of multiple single digital twin systems. To federate the multiple single digital twin systems, single digital twin management, validation and federation techniques are required. Therefore, proposed methodology suggests the architecture and functions of the digital twin federation system.